Pengaruh Pengawasan Dan Teamwork Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada BPJS Kesehatan Cabang Kota Bukittinggi - Putra, Rio Andhika (Riset Sinergi Indonesia, 2025)
This study aims to examine the effect of Supervision and Teamwork on Employee Performance through Job Satisfaction as an intervening variable using primary data obtained by distributing questionnaires to 57 employees as respondents, namely at the BPJS Kesehatan branch of Bukittinggi City. In this study using Partial Least Square (PLS). The results of this study indicate that Supervision and Teamwork have a positive and significant effect on Job Satisfaction, there is a positive and significant effect between Supervision on Employee Performance, Teamwork has a negative and insignificant effect on Employee Performance, Satisfaction has a positive and significant effect on Employee Performance, there is a negative and insignificant effect between Supervision on Employee Performance through Job Satisfaction, and there is a positive and significant effect between Teamwork on Employee Performance through Job Satisfaction.